Optimasi Perencanaan Produksi Usaha Keripik Sanjai Rina Menggunakan Pendekatan De Novo Programming - Oktavia, Bella; Winanda, Rara Sandhy (UNIVERSITAS NEGERI PADANG, 2023)
One important part of industry is production planning. Production planning is a strategy to determine how many products to produce and how many resources are needed to make these products. By using the De Novo Programming approach, this research aims to determine the right production planning in the Business of Keripik Sanjai Rina so that the maximum profit is obtained. The De Novo Programming approach can determine the best combination of output and proposed use of resources based on the available budget. This approach can be solved using the simplex method. The results showed that the optimal number of products and the amount of raw material purchases were obtained so that the profit obtained by the Business of Keripik Sanjai Rina increased by 35%.